Let them go? How losing employees to competitors can enhance firm status - Tan, David; Rider, Christopher I. (Strategic Management Journal, 2017)
Research summary : Because employees can provide a firm with human capital advantages over competitors, firms invest considerably in employee recruiting and retention. Departing from the retention imperative of strategic human capital management, we propose that certain employee departures can enhance a firm's competitiveness in the labor market. Specifically, increased rates of career‐advancing departures by a firm's employees can signal to potential future employees that the firm offers a prestigious employment experience that enhances external mobility opportunities. Characterizing advancement based on subsequent employers and positions, we analyze data on U.S. law firm hiring and industry surveys of perceived firm status between 2004 and 2013. We find that increased rates of employee departures lead to increases in a firm's prestige when these departures are for promotions with high‐status competitors . Managerial summary : Firms often emphasize employee retention. Employee departures, especially as a result of being hired away by competitors, are often viewed as threats to a firm's competitive advantage. We propose, however, that employee retention need not be an unconditional strategic imperative. We argue that certain employee departures can enhance a firm's competitiveness in the market for human capital by signaling to potential employees that the firm offers a prestigious employment experience, which can help them obtain attractive positions with other employers. Analyzing data on U.S. law firm hiring and industry surveys of firm associates between 2004 and 2013, we find that increased rates of employee departures lead to increases in a firm's prestige when these departures are for promotions with high‐status competitors . Copyright © 2016 John Wiley & Sons, Ltd.